Morphological and agronomic characteristics of winter rye cultivars in connection with their resistance to lodging - N. A. Nabatova; E. S. Parfenova; E. I. Utkina; M. G. Shamova; E. A. Psareva; M. N. Zhukova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Lodging resistance of winter rye is associated with morphological features of the stem. Searching for source material to breed non-lodging high-yielding cultivars requires studying the varietal phenotypic diversity according to morphological characters of the stem that affect the resistance to lodging and the productivity of the ear.Materials and methods. Experiments were carried out in 2017–2020 at the Federal Agricultural Research Center of the North-East (FARC North-East), Kirov. Field resistance to lodging, morphological characteristics of the stem, yield, and ear productivity were evaluated in 16 winter rye cultivars. The study was based on the International COMECON List of Descriptors for the Genus Secale L., and Methodology for the State Variety Trials of Agricultural Crops. The weight of segments of the second lower internodes was measured in 10 plants of each cultivar under laboratory conditions.Results and conclusions. Negative correlations of lodging resistance with stem length (r= –0.55) and the weight of the second lower internode (r = –0.65) were revealed. Ear productivity of rye cultivars was significantly associated with the wall thickness (r = 0.52) and the length of the second lower internode (r = –0.52). According to the results of the path analysis, the main causes of a decrease in lodging resistance were the weight of the segment (P = –0.467) and the length of the second lower internode (P = –0.408), while an increase was connected with the wall thickness of the second lower internode (P = 0.424). The cultivars differed significantly in their resistance to lodging (LSD05 = 0.8). Cvs. ‘Moskovskaya 12’, ‘Tatyana’, ‘Bylina’ and ‘Yantarnaya’ were identified; they are recommended as source material for breeding for lodging resistance.